2021
DOI: 10.5123/s2176-6223202100862
|View full text |Cite
|
Sign up to set email alerts
|

Análise epidemiológica comparativa entre as pandemias causadas pelos vírus Influenza A(H1N1)pdm09 e SARS-CoV-2 no estado do Pará, Brasil

Abstract: Analisar as características epidemiológicas, similaridades e diferenças da influenza A(H1N1)pdm09 e da COVID-19 no estado do Pará, Brasil. MATERIAIS E MÉTODOS: Trata-se de um estudo epidemiológico descritivo, com dados sobre casos e óbitos de influenza A(H1N1)pdm09 coletados no Sistema de Informação de Agravos de Notificação, referentes ao período de junho de 2009 a maio de 2010, e de COVID-19, na Secretaria de Saúde do Estado do Pará, referentes ao período de março a julho de 2020, com a última data da coleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Em 2020 no estado do Pará um estudo registrou picos de COVID e de H1N1, com 61.300 novos casos de COVID-19 e 147 casos de influenza, e em relação à faixa etária as mulheres foram mais acometidas pela influenza 27 .…”
Section: Discussionunclassified
“…Em 2020 no estado do Pará um estudo registrou picos de COVID e de H1N1, com 61.300 novos casos de COVID-19 e 147 casos de influenza, e em relação à faixa etária as mulheres foram mais acometidas pela influenza 27 .…”
Section: Discussionunclassified
“…In Brazil, the incidence of SARS associated with COVID -19 totaled 20.846 cases and 856 deaths in the age group between 0 and 19 years by epidemiological week 51 of 2022 (3). In this context, it can also be observed that children were not initially affected by SARS-CoV-2 as much as in the 2009 pandemic caused by H1N1.…”
Section: Introductionmentioning
confidence: 97%
“…(1) In children, several factors contributed to milder infection, which reduces the number of the significant receptor angiotensin-converting enzyme 2 (ACE2) on the cell surface, resulting in less availability of the receptor, and the presence of other respiratory viruses competing simultaneously and limiting replication of different viruses. In neonates and infants, maternal antibodies provide protective immunity against disease (2,3).…”
Section: Introductionmentioning
confidence: 99%